Protein tyrosine phosphatase non-receptor type 2 as the therapeutic target of atherosclerotic diseases: past, present and future - Tang, Xiao-Er; Cheng, Ya-Qiong; Tang, Chao-Ke (Frontiers in Pharmacology, 2023)
Tyrosine-protein phosphatase non-receptor type 2(PTPN2)， an important member of the protein tyrosine phosphatase family, can regulate various signaling pathways and biological processes by dephosphorylating receptor protein tyrosine kinases. Accumulating evidence has demonstrated that PTPN2 is involved in the occurrence and development of atherosclerotic cardiovascular disease. Recently, it has been reported that PTPN2 exerts an anti-atherosclerotic effect by regulating vascular endothelial injury, monocyte proliferation and migration, macrophage polarization, T cell polarization, autophagy, pyroptosis, and insulin resistance. In this review, we summarize the latest findings on the role of PTPN2 in the pathogenesis of atherosclerosis to provide a rationale for better future research and therapeutic interventions.